1999
DOI: 10.1089/109493199316375
|View full text |Cite
|
Sign up to set email alerts
|

The "Cyberlink" Brain-Body Interface as an Assistive Technology for Persons with Traumatic Brain Injury: Longitudinal Results from a Group of Case Studies

Abstract: A longitudinal study of traumatic brain-injured and comatose participants suggests that these individuals are able to learn to use a mental interface device to navigate a maze and perform some basic communication. The device, known as the "Cyberlink," uses electrooculargraphic, electromyographic, and electroencephlagraphic signals collected at the forehead to control cursor movement. Further details of the operation of the device and the set-up procedures are reported. Six adults, all of whom had traumatic bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…This strategy supported efficient use of training time. A more technically complex approach uses "biosignals", as seen in the use of the "Cyberlink" system (Doherty, Bloor, & Cockton, 1999). Initial results using this system suggested that persons with extreme motor and language impairments following stroke and traumatic brain injury were able to communicate using an EEG/EOG/EMG-driven cursor on a flatscreen computer.…”
Section: The Design Of Safe Testing and Training Environments That MImentioning
confidence: 99%
“…This strategy supported efficient use of training time. A more technically complex approach uses "biosignals", as seen in the use of the "Cyberlink" system (Doherty, Bloor, & Cockton, 1999). Initial results using this system suggested that persons with extreme motor and language impairments following stroke and traumatic brain injury were able to communicate using an EEG/EOG/EMG-driven cursor on a flatscreen computer.…”
Section: The Design Of Safe Testing and Training Environments That MImentioning
confidence: 99%
“…Like the Emotiv neuroheadset, the Brainfingers headband detects EMG, EOG and EEG activity. Doherty et al (1999Doherty et al ( , 2002 trialled the headband on six adults with brain injuries. Over a period of seven months, the participants learned to move a cursor left and right using eye movements, and up and down by controlling their EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…A device called "Cyberlink" can be used to monitor eye movements with electrooculography (EOG), muscle activity with electromyography (EMG), and brain activity with electroencephalography (EEG) [Doherty et al 1999; see also Allanson et al 1999]. Barreto et al [2000] developed a method that combined the use of EOG (from cranial muscles) and EEG (from occipital lobe) signals for two-dimensional cursor movements by applying amplitude thresholds and power spectral density estimations.…”
Section: Introductionmentioning
confidence: 99%